Abandon - Cabot, Meg (Point, 2011)
A near-death experience, a horrible incident at school, and a move from Connecticut to Florida have turned seventeen-year-old Pierce's life upside-down, but when she needs him most John Hayden is always there, helping but reminding her of her visit to the Underworld.